PERLINDUNGAN HUKUM HAK CIPTA BUKU PENGETAHUAN DITINJAU DARI UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Achmad Chosyali (Universitas Kristen Satya Wacana, 2018)
Abstract Copyright is the exclusive right of the creator to announce or reproduce his creations in the fields of science, art, and literature, which among others can consist of books, computer programs, lectures, lectures, speeches and other similar works, as well as rights related to copyright. A book is an intellectual work of a creator or copyright holder who has exclusive rights consisting of two rights, namely economic rights and moral rights so that this right must be protected. Noticing the existence of exclusive rights, the researcher is willing to know about the protection and prospects of the copyright protection of knowledge books are reviewed from Law Number 28 of 2014 concerning copyright. The method used in this study is normative juridical method. With this legal protection, it is expected to be able to provide a better awareness and understanding in the future. Key words: Prospects, Legal Protection, Knowledge Books, Copyright